Diagnosis of human enterovirus A71 infection in Malaysia using a commercial IgM-capture enzyme-linked immunosorbent assay and an IgM-colloidal gold immunochromatographic assay - Aw-Yong, K.L.; Tan, C.W.; Koh, M.T.; Sam, I.C.; Chan, Y.F. (Malaysian Society for Parasitology, 2016)
Hand, foot and mouth disease (HFMD) is a common childhood infection caused by many enteroviruses, including enterovirus A71 (EV-A71). As EV-A71 is associated with severe neurological disease, early diagnosis is critical for clinical and public health management. In developing countries such as Malaysia, laboratory capacity to carry out EV-A71 IgM detection is greater than that of the gold standard methods of virus culture or molecular detection. This study evaluated two diagnostic kits, EV-A71 IgM-capture enzyme-linked immunosorbent (ELISA) and EV-A71 IgM-colloidal gold immunochromatographic assay (GICA), which had previously only been assessed in China. The assays were tested with 89 serum samples from patients with suspected HFMD. The sensitivity, specificity, positive predictive value, and negative predictive value rates were 78.4%, 80.8%, 74.4%, and 84.0%, respectively, for the IgM-capture ELISA, and 75.7%, 76.9%, 70.0%, and 81.6% for the IgM GICA. These performance measures were similar between the two assays. Concordance between the two assays was 91.1%. The sensitivity rates were lower than those previously reported, likely because the multiple circulating EV-A71 genotypes in Malaysia differ from the C4 subgenotype found in China and used in the assays. Both assays had low false positive rates (12.5% and 16.7% for ELISA and GICA, respectively) when tested on sera from patients confirmed to have enteroviruses. Both diagnostic kits are suitable for early diagnosis of HFMD caused by EVA71 in Malaysia, but confirmation with culture or PCR is still important.